kapasitas balok beton geopolymer bertulang dengan variasi dimensi tulangan - prakasiwi, luhur, Ir. Suhendro Trinugroho, M.T, Budi Setiawan, S.T., M.T (2016)
Geopolymer concrete is a kind of concrete that has been using fly ash as a basic sticky materials to substitute cement. To speed up fly ash reaction has been added activator alkaline that has been as silicate sodium and hydrokside sodium with comparition as 5:2. The purpose of this reseach is going to apply geopolymer concrete into structure of bone concrete and also the characteristic of Geopolymer concrete. The bone of beam has used iron D8, D10, D12 and begel 06 with 150 mm as a gap. Mix design of geopolymer concrete has been pointing at with the reseach before, and normal concrete has used a method from ACI with the power of pressure 20 Mpa. The materials that have been examined includes 3 normal cylinder of concrete, 3 cylinder geopolymer of concrete, 3 beam of normal normal concrete and 3 beam of geopolymer concrete. The results of test have shown that normal concrete is better than geopolymer concrete. The weight of normal concrete is 2.261 gr/cm3, meanwhile the weight of geopolymer concrete is lower than normal concrete as 2.125 gr/cm3. The average of pressure power of normal concrete is 18.976 Mpa, little bite lower than the planing before 20 Mpa. The pressure power of geopolymer concrete has achieved 15.864 MPa. The maximum moment of bone of geopolymer concrete beam D8 has been 10,555 KN.M, D10 is 16,030 KN,M , and D12 is 25,075 KN.M. The gap between maximaise moment of bone D8 is 4,351%, D10 is 6,586% and D12 is 2,485%. Base on the data that has been found by the researcher. It is able to be concluded that the quality of normal concrete has been better than geopolymer concrete, although it has been known that normal concrete is not good for environment.